PO 94 - ABORDAGEM ANESTÉSICA NUM DOENTE COM DOENÇA DE MADELUNG – CASO CLÍNICO - Pires Asseiro, Mariana; Mendes, Eunice; Marques, Acílio; Bernardino, Ana (Journal of the Portuguese Society of Anesthesiology, 2023)
x